2017
DOI: 10.1111/jam.13365
|View full text |Cite
|
Sign up to set email alerts
|

Methodological flaws introduce strong bias into molecular analysis of microbial populations

Abstract: The identified weaknesses of commonly used methods to study microbial diversity can be overcome by a multi-level approach, which produces more reliable data about the fate and behaviour of microbial communities of engineered habitats such as biogas plants, so that the best performance can be ensured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…2A ). Slower growth was reported with plant slurry preparations, and may be attributed to their concentrated nutritional contents creating osmotic stress environments ( 8 , 24 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A ). Slower growth was reported with plant slurry preparations, and may be attributed to their concentrated nutritional contents creating osmotic stress environments ( 8 , 24 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Advances in molecular biology techniques with the development of culture-independent techniques have highlighted the joint genomic, transcriptomic, and proteomic interactions that influence the culturability of microorganisms ( 47 ). Despite the high-throughput nature of these culture-independent approaches for community profiling ( 42 ), previous studies demonstrated their inherent bias that results in a superficial view of microbial community compositions ( 24 ). Unculturable populations account for more than 90% of a given ecosystem, and represent diverse groups of microbes with overlooked functional niches.…”
mentioning
confidence: 99%
“…How is it that a single extraction procedure can portend to achieve a uniform and balanced extraction? In the process of establishing this ddPCR procedure it was found that Listeria DNA was poorly extracted, quite probably due to the stronger cell wall, compared to gram–bacteria (Krakat et al, 2017 ). Optimization was eventually achieved by sonication.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, QPCR data representative of each pathogen level in a sample requires efficient extraction and amplification of DNA from each of the pathogens. However, the DNA of L. monocytogenes , like most gram positive organisms, is difficult to extract with the same efficiency as gram negative organisms (Krakat et al, 2017 ). This problem impacts not only QPCR of pathogens but also several other quantification methods, such as metagenomics, where samples are known to include a host of unknown organisms and probably both gram + and gram –bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…While this information complements nicely the DNA‐based information detailed above, abundance differences for the same phylogenetic group using different methods (e.g., single cell based versus sequencing based) might appear. This can be assigned to the sample processing, as for instance the DNA‐based sequencing methods are partly biased due to different DNA extraction and amplification, and FISH can be biased due to fixation and hybridization efficiency differences (Amann and Fuchs, ; Krakat et al ., ).…”
Section: Application Of Microbial Ecology To Metmentioning
confidence: 97%